Coating nanoparticle-assembled Si microspheres with carbon for anode material in lithium-ion battery. (January 2019) - Qu, Fangmu; She, Guangwei; Wang, Jiantao; Qi, Xiaopeng; Li, Shengyang; Zhang, Shaoyang; Mu, Lixuan; Shi, Wensheng
Abstract: The large volume changes of Si hamper its commercial application in lithium-ion battery (LIB) although extraordinary specific capacity of the Si has been theoretically demonstrated. The Si-based anodes with micro-nano hierarchical architecture can overcome the disadvantage of Si. In this work, Si microspheres (SiMS) with micro-nano hierarchical architecture were inexpensively coated with pitch carbon via facile solution process and subsequent thermal carbonization, and the C-SiMS were finally obtained. The Si nanoparticles were of benefit to the stress relief and the interspaces between the silicon nanoparticles could availably accommodate the volume expansion. The amorphous carbon coated on the SiMS would provide a potent barrier between the Si and electrolyte. Used as anode material in LIB, the C-SiMS exhibited enhanced initial coulombic efficiency and cycle stability. This research provides an efficient and low-cost method for mass production of silicon anode materials. Graphical abstract: Highlights: Nanoparticle-assembled Si microspheres (SiMS) were coated with carbon for LIB. Low-cost raw materials (SiMS and pitch) and facile processes. The unique structure of C-SiMS can effectively accommodate volume expansion of Si. The C-SiMS exhibit high initial coulombic efficiency and improved cycle stability.